2016
DOI: 10.1371/journal.pone.0161995
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Adherence of Tuberculosis Patients Attending Two Reference Units in Equatorial Guinea

Abstract: Equatorial Guinea has one of the highest burden of tuberculosis (TB) in Africa. Incomplete adherence to TB treatment has been identified as one of the most serious remaining problem in tuberculosis control. The following study is aimed at determining the adherence to anti-tuberculosis treatment in Equatorial Guinea and its determinants, as well as at assessing the knowledge of the people about the disease. In this cross-sectional study, participants were recruited by non-probabilistic consecutive sampling amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
16
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 22 publications
10
16
0
7
Order By: Relevance
“…All these variables were without impact between adherent and nonadherent patients, while the knowledge about whether TB is cured was significant between these two groups of patients. Similar results found other researchers presenting inadequate level of TB knowledge in patients in Equatorial Guinea [ 28 ] and Ethiopia [ 30 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…All these variables were without impact between adherent and nonadherent patients, while the knowledge about whether TB is cured was significant between these two groups of patients. Similar results found other researchers presenting inadequate level of TB knowledge in patients in Equatorial Guinea [ 28 ] and Ethiopia [ 30 ].…”
Section: Discussionsupporting
confidence: 91%
“…We also found that education level and employment do not play a role in TB treatment adherence. Nevertheless, the educational attainment usually is correlated with patient's TB knowledge and seems to have an impact on TB treatment adherence, while the employment does not have an effect [ 22 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Direct association between educational level and perceptions was positive and significant. It is in accordance with the result of previous study that mentioned that there was an association between educational level and perceived benefit in which it influenced adherence toward treatments (Fagundez et al, 2016).…”
Section: The Association Between Perceivedsupporting
confidence: 92%
“…Previous studies have found that individuals with higher socioeconomic status have greater awareness and knowledge of TB [18], and are less likely to have delay in the diagnosis and treatment of TB [19]. Furthermore, prior reports showed that TB patients with higher socioeconomic status are more likely to have good adherence to TB treatment [20, 21], which could reduce the mortality during TB treatment. To improve TB treatment outcomes, future control programmes should target particularly patients who had a lower socioeconomic status.…”
Section: Discussionmentioning
confidence: 99%